Understanding the Entry Points for Improving the Smallholder Chicken Production in sub-Saharan Africa - Goromela, E.H.; Sonaiya, Emmanuel B.; Assefa, G.; Mbaga, S.H.; Adebambo, Ayotunde Olufunmilayo; Abegaz, Solomon; Bamidele, O.; Esatu, Wondmeneh; Alemayehu, T.; Bruno, J.; Poole, Elizabeth J.; Getachew, Fasil; et al. (2019)
A baseline survey involving 3,714 poultry keeping households (PHH) in 220 villages across five agro-ecological zones was conducted in three countries: Ethiopia (ET), Nigeria (NG) and Tanzania (TZ). The objective was to characterize the smallholder chicken production system and the socio- economic status of PHH. Data were analysed for the gender and age of the household heads, gender of respondents, sources of income, asset ownership, and agro-ecological location of PHH. The results show that 23% (20% ET, 26% NG and 21% TZ) of the PHH had a female as head. Crops, livestock and poultry were the main sources of income for ET and TZ while, in Nigeria, crops, trading and services were the main sources. The contribution of livestock to household income in Ethiopia (38.5%) was higher than in Tanzania (15.6%). More than 70% of PHH had adequate food in the last 12 months (85% ET, 70% NG and 89% TZ). Chicken meat consumption per PHH was 2.9 birds in 3 months (1.8 ET, 4 NG and 3 TZ), while egg consumption was 17 eggs in 3 months (22 ET, 14 NG, 14.6 TZ). The average flock size was 22 (9 ET, 30 NG, 27 TZ) and egg production was 10 eggs per clutch. The PHH desire were to have birds with good physical appearance, large body size and fast growing in cocks and high egg production and hatchability in hens. Information from the survey informed the design and implementation of the longitudinal study.